In Vitro Shoot Induction of Musa acuminata cv. Mas Kirana - Raden Roro Rifka Annisa; Arkan Setiaji; Aries Bagus Sasongko (Quagga : Jurnal Pendidikan dan Biologi, 2020)
Abstract: The availability of ‘mother plants’ used for source of explants is one of the most important limitations for the development of in vitro culture in new banana cultivar’s. To increase produce large quantities of uniform and healthy seedlings, induction of multiplication has been carried out on Musa acuminata cv. Mas Kirana. Plant regeneration were obtained by culturing sucker on MS medium supplemented with PGRs BAP and NAA (1 mg/l + 0.5 mg/l, 2 mg/l + 0.5 mg/l, and 3 mg/l + 0.5 mg/l) and TDZ (0.25 mg/l, 0.5 mg/l, and 0.75 mg/l). The highest shoot formation was found in 0.25 mg/l TDZ with average shoots of 13.67 ± 3.16 and primary shoot height is 20 cm. TDZ induction tends to form somatic embryos, while induction of BAP and NAA leads to organogenesis. The rate of contaminants occurrence from bacteria is 87.50% and 12.50% from fungus. In histological observation, TDZ, BAP, and NAA affect the development of many new meristematic zones seen in the scalps.